Framing the Virtual (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Immersive exhibitions have a long history in art. The metaphor of immersion implies a plunge into an all-encompassing environment, where audiences are seemingly transported into alternate virtual realities. From panoramas and 3D cinemas to site-specific installations and performances, a wide variety of mediums, practices, and sites have framed immersive experiences in exhibition contexts. Emerging technologies have also played a significant role in this history, as their capabilities assist in the transformation of “real” space into “virtual” space. This Special Issue of Arts considers the role of new technologies in facilitating immersive art exhibitions. How do histories of technology intersect with histories of immersion and the virtual? How do new technologies influence artistic practices such as installation art, performance, or exhibition design? How does technology—broadly defined—impact how audiences experience and interact with exhibition spaces?